STANCE COMPLEMENT CLAUSES CONTROLLED BY ADJECTIVES IN ESL AND EFL STUDENTS' ARGUMENTATIVE ESSAYS - Faiz, Adinda; Munandar, Aris (Universitas Muhammadiyah Metro, 2025)
Stance becomes an important evaluative discourse feature that aids writers in conveying their arguments effectively. Studies have focused on comparing the stance of non-native speakers of English to that of native speakers and have not yet addressed the issue between English learners from different contexts. This study analyzes stance complement clauses controlled by adjectives by Singaporean ESL and Indonesian EFL students. It aims to uncover the frequency and distribution of stances and to explain why Singaporean students' stances differ from those of their Indonesian EFL counterparts. This study used quantitative and qualitative methods. The chi-squared test was carried out to determine whether there was a significant difference. The data were extracted from a sub-written ICNALE corpus, the essays by Singaporean and Indonesian students at the B1_2 level. The chi-squared test indicates there is a significant difference. The results reveal a higher use of stance adjectives among Singaporean ESL students compared to Indonesian EFL students. This study has important implications. Explicit teaching and learning of stance features used adequately in the argument's structure are needed, especially highlighting adjectival repertoire for variety and nuance to the EFL students' stance.